The Use of Drilling Technique to Teach English Speaking to the Early Childhoods: A Descriptive Study - Yusuf Hidayat; Ani Herniawati; Nu’man Ihsanda (Journal Corner of Education, Linguistics, and Literature, 2022)
Teaching English speaking to the early childhoods requires optimal efforts and special tricks. The teacher requires appropriate teaching technique and media to make them enjoy during learning English speaking. This research attempts to report what appropriate technique and media applied by the teacher during teaching English speaking to the early childhoods in one of English courses in Ciamis - West Java. In this research, the researchers set forth two research questions, they are what teaching technique is appropriately applied to teach English speaking to the early childhoods? And what media are suitable to teach English speaking to the early childhoods? To answer the aforementioned research questions, the researchers employ a qualitative descriptive study at which they observe the process of teaching and learning English towards a group of the early childhoods during February - June 2019. The results of the research reveal that drilling is selected as the appropriate technique under the Audio-Lingual Method applied by the teacher during teaching English speaking to the early childhoods. Meanwhile, song is selected as the appropriate media applied by teacher during teaching English speaking to the early childhoods. In conclusion, through employing drilling technique and song, the process of teaching English speaking to early childhoods becomes more fun, so that their English speaking skill is improved.